Multiplicidade sancionatória estatal pelo mesmo fato : ne bis in idem e proporcionalidade - Bach, Marion (2021)
This study has been inspired by the (current) ascertainment that the State sanctions the same fact multiple times: through both administrative law, which has become more sanctioning in recent years, and criminal law itself, which in turn has acquired more and more characteristics of administrative law. Due to their attachment to the (debatable) mantra of independence between the different instances, both Brazilian doctrine and jurisprudence do not tackle the topic with due diligence. Therefore, the aim of this research is to understand the phenomenon of the State’s sanctioning multiplicity – known in the United States as the “piling on” of fines and penalties – as well as draw the (difficult, but necessary) distinction between a criminal offense and an administrative offense. Afterwards, not without taking into consideration the Brazilian legal scenario, the focus will be shifted to settling presuppositions related to the principles of ne bis in idem (double jeopardy) and proportionality. Finally, and as a means to an end, the answers to two questions will be provided, the first one being: whenever the State sanctions, due to the same fact, multiple times, will the principle of ne bis in idem be violated? The answer to this inquiry can be provided, briefly, in this very abstract: not always. There are illegitimate sanctioning cumulations, but there are also legitimate ones. This research lists, based on decisions of international tribunals and courts, criteria apt to verify said (il)legitimacy. From the answer to the first question comes the second one: whenever the State rightfully sanctions, due to the same fact, multiple times, will the principle of proportionality be violated? Once again, the question can be briefly answered in this summary: the automatic and unadvised overlaid sanctioning – coming from all instances – does violate the principle of proportionality, thus making it urgent not only to focus on the applicable state sanctioning set to the same fact, but also to indicate (concrete) ways for the application of multiple sanctions to achieve unavoidable proportionality. These are the aims and objectives of this research.